Studio Acusticum : a concert hall with variable volume - Öqvist, Rikard; Ågren, Anders; Tunemalm, Björn (Luleå tekniska universitet, Drift, underhåll och akustik, 2008)
In the town of Piteå in the north of Sweden a new multipurpose concert hall, Studio Acusticum, was inaugurated in 2007. The acoustics of the hall is designed by Tunemalm Akustik with some help from Luleå University of Technology. Since Piteå is a town with a strong tradition of using wood for buildings, the construction consists mostly of wood. Surface treatment of the wooden elements permits good reflective properties. What makes this hall special is that the variable acoustics is accomplished by a height adjustable ceiling which can be raised or lowered 5 m, thereby effectively changing the reverberation volume by 30 %. There are also absorptive curtains which can be lowered to achieve short reverberation times for electronically amplified music. When compared to other multipurpose halls, this solution provides good acoustics for all uses without the need to compromise. A change in volume affects the reverberation time equally on all frequencies which gives better results than added absorption. Also, measurements have shown that reverberation time and clarity are the only parameters that change when the ceiling is lowered. Loudness, Lateral fraction and IACC are not affected by the change in ceiling height. This paper will give a thorough presentation of Studio Acusticum and its acoustical properties. Godkänd; 2008; 20081106 (ricokv)